The Contribution of Islamic Commercial Banks to Indonesia’s GDP: Evidence from Third-Party Funds and Working Capital Financing - Rizal, Fitra; Mukaromah, Haniatul (El-Barka, 2024)
The growth of Islamic banking in Indonesia has continued to increase. Yet, its market share remains relatively small compared to conventional banks, resulting in a suboptimal contribution to the national economy. This study aims to analyze the contribution of Islamic Commercial Banks to Gross Domestic Product (GDP) through Third-Party Funds (DPK) and Working Capital Financing (PMK), with Return on Assets (ROA) as an intervening variable. The study employs a quantitative approach using quarterly secondary data for the 2015–2022 period obtained from the Financial Services Authority (OJK) and Statistics Indonesia (BPS). Data analysis was conducted using multiple linear regression and the Sobel test to examine direct and indirect effects. The findings reveal that DPK has no significant effect on ROA, while PMK significantly impacts ROA. Furthermore, DPK and PMK significantly influence GDP, whereas ROA has no significant impact on GDP and does not serve as an intervening variable. These results highlight that the contribution of Islamic Commercial Banks to economic growth is primarily driven by their financing intermediation function rather than bank profitability.